The development of UMClubLearn website as an income generation and entrepreneurship ecosystem for Faculty of Sport Science - Prisca Widiawati; Jacobus Wiwin Kuswinardi; Febrita Paulina Heynoek; Supriatna; Alfan Zuhair Dinata; Purwadi, Dinda Arisetya (Indonesian Journal of Sport Management, 2024)
Sports coaching education faces challenges in producing graduates who are competent in soft skills and entrepreneurship. Graduates are expected to compete in a highly competitive job market. This study aims to develop the UMClubLearn website as a learning center for students and the general public to enhance soft skills, entrepreneurial knowledge, and certification in sports. The research method used is research and development (R&D) with the ADDIE model. The study sample involved 337 undergraduate students from the Department of Coaching Education at Universitas Negeri Malang. The data were collected through questionnaires consisting of needs analysis, expert validation of the material, and product trials.  The analysis results showed that the UMClubLearn website achieved a very high level of validity, with an average score of 92% from material experts and 83% from media experts. Small and large group product trials also showed scores of 81% and 83%, respectively, indicating that the website is user-friendly and functional. The conclusion of this research is that the development of the UMClubLearn website fits the students' needs in soft skills and entrepreneurship development and has the potential to be a comprehensive solution in coaching education. Through this platform, it is expected that a new generation of competent sports coaches and entrepreneurs will emerge, ready to face challenges in the industrial field. The practical implications include enhancing accessibility to quality education and training, while theoretical implications suggest the integration of technology in sports education can bridge existing gaps in traditional training methods.